Dynamics of Corporate Finance Research in Global Scientific Literature - Yahya, Lucky Mahesa; Sudarmanto, Eko (Westscience Press, 2024)
This study explores the dynamics of corporate finance research in global scientific literature from 2000 to 2024 using a bibliometric approach. By analyzing keyword co-occurrence and citation data, the research identifies key themes, emerging trends, and influential contributors in corporate finance. Core topics such as capital structure, cost management, and debt remain central, reflecting traditional corporate finance priorities. However, newer areas, including corporate social responsibility (CSR), corporate cash holdings, and behavioral finance, have gained prominence, signaling a shift towards integrating non-financial factors into corporate strategies. The study also highlights the lasting impact of global financial crises, particularly the 2008 crisis, on shaping research in financial distress, risk management, and institutional roles. These insights provide a comprehensive overview of the evolution of corporate finance research and offer directions for future studies.